PCB biodegration using bacteria isolated from landfill leachate - Nordin, Noor Faizul Hadry; Mohd Idris, Siti Nur Nadiah; Mohd Nawi, Mohd Nazri; John, Akbar; Chowdhury, Ahmed Jalal Khan (RAZI Publishing, 2017)
Polychlorinated biphenyls, PCBs are toxic, persistent organic pollutants (POP) which are harmful to human and environment due to their lipophilic characteristic and not easily degraded in the environment. Biodegradation is one of the alternative ways to reduce PCBs contamination. This study intended to isolate bacteria from landfill leachate using enrichment culture technique and optimize the growth condition of selected isolates for degradation of PCBs. PCB biodegradation efficiency by selected bacterial isolates was also determined using GC-MS. Three potential PCBs degraders were isolated from the samples of landfill leachate through enrichment culture technique, which utilised PCBs as sole carbon and energy sources but only isolate T12B shown significant effect on the degradation. Three different growth parameters were optimized involving the temperature, pH, and PCBs concentration. Central composite design (CCD) from Design Expert Software was used to design the experiment. The optimal growth condition of temperature at 37˚C with 10 ppm of PCB concentrations and pH 8 for the culture medium was achieved using Response Surface Methodology (RSM) analysis. Based on GC-MS analysis, the reduction of PCBs concentration indicates that they were utilized by isolates T12B as sole of carbon and energy sources. This may suggest that bacteria in landfill leachate play an important role in biodegradation process as well as more effective and economical.